Synthesis and characterization of Egg shell (ES) and Egg shell with membrane (ESM) modified by ionic liquids - Haddad, Boumediene; Mittal, Alok; Mittal, Jyoti; Paolone, Annalisa; Villemin, Didier; Debdab, Mansour; Mimanne, Goussem; Habibi, Asmaa; Hamidi, Zineb; Boumediene, Mostefa; Belarbi, El-habib (Chemical Data Collections, 2021)
•Chemical modification of Egg shells (ES) and Egg shells with membrane (ESM) by ionic liquids firstly reported.•Structural, spectroscopic and thermal properties of these ES and ESM by XRD, FTIR and TG/DTA.•The chemical modification by both ionic liquids and protein contents increased the thermal stability of ES and ESM.•Potential application of modified ES as eco-friendly candidate for adsorption process. Egg shell (ES) is a biological macromolecule mainly containing calcite embedded in proteins and polysaccharides, while shell membrane predominantly contains proteins. Thus ES with membrane (ESM) possesses richer protein contents than ES. In the present work, ES and ESM have been separately modified using mono- and di- cationic imidazolium ionic liquids, [C5mim+][Br−] (IL) and [Bis-(PhCH2MIm)+][2Cl−] (DIL). Thus four modified products have been obtained namely ES-IL, ES-DIL, ESM-IL and ESM-DIL. In order to determine physico-chemical modifications of the ES due to the interactions with the ionic liquids, the structural, spectroscopic and thermal properties of all products were investigated by means of XRD, FTIR and TG/DTA. The IR spectra display significant changes in the 1400 – 1550 and 2800 – 3100 cm−1 regions confirming the insertion of IL and DIL into the ES and ESM layers. Furthermore, the XRD results indicate that this modification process influence the crystal structure of the ES. Thermal analysis suggests that the chemical modification increases the thermal stability of the ES and ESM. It has also been ascertained that presence of proteins in the shell membrane is responsible for increasing thermal stability in the order ES < ESM < ES-IL < ESM-IL < ES-DIL < ESM-DIL. [Display omitted]